Extraction of Manganese Ore from East Nusa Tenggara-Indonesia for Production of Mn(II)-Terephthalate and Mn(II)-Tartrate Coordination Polymers - Abi, Faustina De Yesu Prisila; Tjahjanto, Rachmat Triandi; Prananto, Yuniar Ponco (UIR PRESS, 2025)
Pyrolusite, a manganese ore from East Nusa Tenggara (Indonesia), was explored and utilized in the production of crystalline Mn(II) based coordination polymers materials, namely Mn(II)-terephthalate and Mn(II)-tartrate. The pyrolusite was extracted into Mn(II) sulfate by acid method in the presence of hydrogen peroxide. The Mn(II) sulfate, characterized by X-ray fluorescence (XRF), infrared spectroscopy (IR), and X-ray powder diffraction (PXRD), was then used as a precursor in the production of crystalline Mn(II) based coordination polymers materials using a solution method at room temperature. Two ligands, terephthalate and tartrate, were used separately, in which the terephthalate complex was prepared using a layered solution technique, while the tartrate complex was made using a direct mixing technique. The synthesized Mn(II) coordination polymers were then characterized by FTIR and PXRD. This study finds that the manganese ore was extracted as MnSO4 compounds with purity of 96.88% and average crystallite size of 103 nm. The MnSO4 was successfully converted into crystalline Mn(II) coordination polymers materials. Based on IR and PXRD analyses, the crystalline products were identified as Mn(II)-aqua-terephthalato and Mn(II)-aqua-tartrato hydrate complexes, in which the former complex display 3D networks and the latter complex display 2D sheets of polymeric structures.